ANALYSIS OF FACTORS AFFECTING GUEST DECISION IN PURCHASE OF ROOM SERVICE IN HOTEL “GRAND INNA PADANG” - Abrian, Youmil; Adrian, Arif; Surendra, Rian (Journal of Business on Hospitality and Tourism, 2019)
This paper was conducted to determine what factors encourage consumer decisions in choosing Grand Inna Hotel Padang, as well as the contribution of each of these factors. Researchers used the Grand Inna Hotel Padang because the hotel is owned by the government. Grand Inna Hotel Padang has unstable occupancy then affects to the hotel revenue. The results showed that there are 7 factors considered by consumers in rooms purchasing  Grand Inna hotel Padang, the 7 factors mentioned are price factors,  service factors, motivation and lifestyle factors, reference group factors, hospitality factors, MICE and brand image. Each of these factors contributes substantially to encouraging consumers to choose Grand Inna hotel Padang. The population of the study was consumers who had stayed at the Grand Inna  Hotel Padang. The sampling technique used purposive sampling with a total sample is 100 respondents. The data analysis technique is factor analysis to determine the factors considered by consumers and multiple regression analysis to determine the extent factors considered affect the purchasing decision. From the results of multiple regression analysis found that the 7 factors together have a significant effect on decision in decisions purchase room service at the Grand Inna Hotel Padang.